(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In fact the government started implementing the poverty alleviation program from the third five-year plan itself; But due to lack of proper implementation, they could not be fully successful. According to some experts, the various programs of rural development planned by the government to eradicate poverty should not be kept under the control of the Panchayat Samiti but should be controlled by a special Development Council. Small, marginal, farmers, artisans and farm laborers should be represented on this development council. Unless there is a complete change in the composition of the Development Council, it is impossible to properly implement the program designed for the welfare of the poor. Poverty alleviation programs will not succeed unless the existing bureaucratic nexus of landlords, capitalists and politicians is broken. For these programs to be successful, it is necessary to create a People’s Development Council.